2011
DOI: 10.1007/s00367-011-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulsed Atlantic water inflow into the Alboran Basin at the time of the Zanclean flooding

Abstract: International audienceThe study of more than 500 single- and multi- channel seismic records enabled the generation of a detailed palaeo-bathymetric map of the Messinian surface over most of the Alboran Basin, Western Mediterranean. This regional surface is characterized by several erosional features (channels, terraces and canyons) and topographic highs (structural, volcanic and diapiric in origin). The most prominent feature is the incised Zanclean Channel crossing the entire basin, its entrenchment having be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 43 publications
5
87
0
Order By: Relevance
“…In the south, over the São Paulo Plateau, the entering sea eroded wide stretches of reworked carbonates, while avalanches of carbonates and Mg-rich shales were sliding down near faults from temporary islands into the deeper portions of the former lakes (de Paula, oral comm.). Similar phenomena were observed east of Gibraltar in the Mediterranean as the major drop of sea level in the Messinian was followed by re-entrance of the sea (Estrada et al, 2011;Rabineau et al, 2015). Both the thickness and width of the salt body increase southward, reaching, respectively, 1-2 km and about 700 km in the Santos Basin (Fig.…”
Section: A N U S C R I P Tsupporting
confidence: 71%
See 1 more Smart Citation
“…In the south, over the São Paulo Plateau, the entering sea eroded wide stretches of reworked carbonates, while avalanches of carbonates and Mg-rich shales were sliding down near faults from temporary islands into the deeper portions of the former lakes (de Paula, oral comm.). Similar phenomena were observed east of Gibraltar in the Mediterranean as the major drop of sea level in the Messinian was followed by re-entrance of the sea (Estrada et al, 2011;Rabineau et al, 2015). Both the thickness and width of the salt body increase southward, reaching, respectively, 1-2 km and about 700 km in the Santos Basin (Fig.…”
Section: A N U S C R I P Tsupporting
confidence: 71%
“…A C C E P T E D (Estrada et al, 2011;Bache et al, 2012;Rabineau et al, 2015). These canyons may have connected to either rivers outside the basin or the proto-Equatorial Atlantic, but the uplift of NE-Brazil in the Tertiary does not allow following the connections.…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…In the western Moroccan margin, Tesson et al (1987) firstly defined two sedimentary sequences, B (Pliocene) and A (Quaternary), bounded by a regional unconformity above the acoustic basement. Later, higher resolution regional studies Campillo et al, 1992;Ercilla et al, 1994;Hernández-Molina et al, 2002) indicated that Pliocene-Quaternary sequences are bounded by a strong, laterally continuous reflector that corresponds to the reflector M (i.e., the Messinian erosion surface, recently mapped throughout the Alborán Sea by Estrada et al, 2011). Three main key reflectors divide the Pliocene-Quaternary deposits into four seismic sequences; P1, top of the lower Pliocene; P2, top of upper Pliocene; and Q1, top of the Calabrian deposits.…”
Section: Structural Setting and Stratigraphymentioning
confidence: 97%
“…Seismic stratigraphy shows a prominent flat wave-cut surface interpreted as erosional features carved during the refill, which argues for a slow initiation of the refill . However, to explain the prominent erosional trough observed in the Alboran Sea (a feature that is revealed by seismic stratigraphy as deeper than 300 m, wider than 6 km in places, and at least 200 km long; Estrada et al, 2011), the flood's 9 feedback should eventually lead to a water discharge close to 10 8 m 3 /s, vanishing the level difference across the Gibraltar threshold in no more than a few years ( (Loget et al, 2015). This will go hand-in-hand with multiscale seismic imaging of basin fill and the crustal and upper mantle structure through a combination of multichannel and wide-angle seismic profiling, and the deployment of novel seismic instrumentation (including the Mermaid system of floating seismometers (Jones, 2014) and the European Plate Observing System (EPOS)).…”
Section: The Gulf Of Lion-sardinia Margins System: a Unique Natural Lmentioning
confidence: 99%